VALUE ENGINEERING ANALYSIS OF BUILDING UPPER STRUCTURE FOR COST EFFICIENCY - Nemesius Bambang Revantoro, Ardhian Alamsyah Prasetya Putra (Universitas Negeri Malang, 2021)
Abstract: Value engineering is the process of identifying alternatives that can provide the same functionality at the same or better level as the original plan while reducing costs and increasing benefits. The research was conducted at the Phase 3 development project of the Islamic University of Islam Malang) because there was a difference between the initial contract fee of Rp. 28,102,142,530 and the change order contract of Rp 20,875,433,588 in upper structure. The aims of the research are: (1) to describe the Development Project of the Islamic University of Malang Islamic Hospital Phase 3; (2) Identifying work items on the upper structure at the information stage; (3) Proposing alternative work items for the upper structure to be analysed by value engineering at the creative stage; (4) Analysing alternative work on the upper structure at the analysis stage; (5) Recommend alternative top structure work items through simulation at the recommendation stage; (6) Describe the level of differences in the structure budget plan for the project and the structure budget plan for value engineering. The research design uses descriptive research design and comparative methods using primary primers such as working drawings, work plans and requirements, and budget plans. The results of the research are: (1) The Islamic University of Malang Islamic Hospital Development Project Stage has a structured budget plan of Rp. 20,875,433,588.49; (2) Alternative work items are given, namely 40/70 for main beams, 30/50 for joists, and floor slabs; (3) The alternative proposed is main beam 35/70 diameter of 19 reinforcement, main beam 40/70 diameter of 16 reinforcement, joist beam 25/50 diameter of 19 reinforcement, joist beam 30/50 diameter of 16 reinforcement, HCS floor plate, flat floor plate palace; (4) Analysis of work alternatives shows that the cost of a 35/70 beam with 19 reinforcement diameter is IDR 3,580,322,171, while a 40/70 beam with 16 reinforcement diameter is IDR 3,410,727,402. Beam 25/50 diameter of reinforcement 19 is Rp. 3,505,187,178, while beam 30/50 diameter of reinforcement 16 is Rp. 3,403,995,232. The HCS precast plate is Rp. 4,647,951,520, while the non-palace plate is Rp. 5,431,891,666; (5) The selected alternative and recommended to the owner are main beam 40/70 diameter of reinforcement 16 with a saving of 16.4%, joist beams of 30/50 diameter of reinforcement 16 with a saving of 12%, and HCS precast plate with a saving of 3%; (6) There is no significant difference between the project budget plan and the value engineering budget plan.Keywords: Upper structure, Value Engineering, Beams, Slabs